Histopathological changes in androgenized ovaries are recovered by melatonin treatment - Souza, Bianca R. de [UNESP]; Almeida Chuffa, Luiz Gustavo de [UNESP]; Simao, Vinicius Augusto [UNESP]; Camargo, Isabel C. C. [UNESP] (Wiley-Blackwell, 2018)
Nandrolone decanoate (ND) is a synthetic steroid, which promotes adverse effects on the ovarian tissue, and melatonin (MLT) exhibits a number of beneficial properties in the reproductive system. This study evaluated the general features of the ovarian tissue and the immunoexpression of sex steroid receptors in ND-treated rats that were submitted to short-term melatonin treatment. Adult rats received mineral oil (control group) and ND at doses of 7.5 mg/kg for 15 days (ND-treated group). The treatment with MLT (10mg/kg for 7 days) was given alone, before or in combination with ND. All ND-treated animals showed persistent dioestrus. In the androgenized groups that received MLT, ovarian morphology and size, and the number/area of corpora lutea were recovered. The number of healthy and atretic follicles was recovered when MLT was administered prior to ND; this was similar to the ovaries of control and MLT groups. There was a decrease in estrogen receptors immunostaining in the follicles of androgenized rats that were treated with MLT, and pretreatment with MLT reduced the expression of androgen receptor in atretic follicles and corpora lutea, when compared with ND-treated group. We conclude that MLT treatment recovered the histopathological aspects of the androgenized ovaries, and MLT pretreatment was the most effective.
Keywords: melatonin; morphometry; nandrolone decanoate; ovarian histology; sex steroid receptors